2014
DOI: 10.1002/acn3.142
|View full text |Cite
|
Sign up to set email alerts
|

Human brain arteriovenous malformations express lymphatic‐associated genes

Abstract: ObjectiveBrain arteriovenous malformations (AVMs) are devastating, hemorrhage-prone, cerebrovascular lesions characterized by well-defined feeding arteries, draining vein(s) and the absence of a capillary bed. The endothelial cells (ECs) that comprise AVMs exhibit a loss of arterial and venous specification. Given the role of the transcription factor COUP-TFII in vascular development, EC specification, and pathological angiogenesis, we examined human AVM tissue to determine if COUP-FTII may have a role in AVM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…After birth, it can still regulate the growth, differentiation, and life cycle of endothelial cells. An increasing amount of data have demonstrated that NFATc1 regulates vasculogenic responses (17,18). A study using vascular endothelial growth factor (VEGF) to induce angiogenesis revealed that NFATc1 is a key component distributed at the merge point of the VEGF-induced vasculogenic endothelial cell escape pathway.…”
Section: Introductionmentioning
confidence: 99%
“…After birth, it can still regulate the growth, differentiation, and life cycle of endothelial cells. An increasing amount of data have demonstrated that NFATc1 regulates vasculogenic responses (17,18). A study using vascular endothelial growth factor (VEGF) to induce angiogenesis revealed that NFATc1 is a key component distributed at the merge point of the VEGF-induced vasculogenic endothelial cell escape pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well known that human brain AVMs overexpress COUP-TFII, PROX1, and other genes, also known to regulate key aspects of angiogenesis and lymphangiogenesis. These genes have similar expression patterns and a subset of them significantly correlated with the presence of preoperative edema and acute hemorrhage (Shoemakerl et al, 2014). STK4 is not included among these genes, but homozygous nonsense mutation in STK4 cause primary immunodeficiency syndrome, given its central role in immunity (Abdollahpour et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with its function in vessel identity specification, increased COUP-TFII expression, paralleled by modifications of SOX18 and Prox1, is associated to brain arteriovenous malformations (AVM) in humans [128,129]. Anatomically, AVM are a net of dysplastic blood vessels without capillaries between the venous and arterial compartments.…”
Section: Coup-tfii and Diabetesmentioning
confidence: 85%
“…The importance of COUP-TFII in endothelial identity is well documented; the choice of arterial versus venous fate is a result of a cross-talk between Notch and COUP-TFII signaling, while the interactions of Brg1, Prox1 and COUP-TFII are central for lymphatic development [96,100,111,204]. The ability to direct angiogenesis is paralleled by its role in mesenchymal cell differentiation and point to a role of the NR in regulating the cells micro-environment with evident implications for several pathologies [45,54,74,95,117,128,132,146]. Indeed, the NR expression (or the absence thereof) is associated with the unfavorable progression of malignancies in several organs [157,163,165,167,173,181]; besides, COUP-TFII is linked to pathologies considered cancer risk factors, such as diabetes or cirrhosis [54,64].…”
Section: Discussionmentioning
confidence: 99%